Peran Pustakawan Data dalam Meningkatkan Literasi dan Kapasitas Pengelolaan Data Penelitian bagi Komunitas Penelitian dan Profesional Informasi di Indonesia - Madiareni Sulaiman; Nur Rizzal Rosiyan; Dwi Untari; Rulina Rachmawati; Cahyo Trianggoro (Media Pustakawan, 2022)
Data librarians are responsible for managing research data, who play an active role in improving the literacy and capacity of the research community and information professionals. Some Indonesian programmes have emerged, but their role and readiness have not been studied. The aspects of personnel readiness to support research data management (RDM) are further discussed in this research, as obligated on the National System for Science and Technology Act No. 11 of 2019. This study was conducted to investigate the readiness of librarians, academic communities, and information professionals in managing research data. A mixed method was used in this research. Firstly, a poll survey was digitally distributed in thematic seminar discussions on data management to librarians and scientists performing RDM tasks. Then, more detailed information about the role of librarians in managing research data was gathered from selected informants on FGD. The study found several points about the role of data librarians in improving data literacy and capacity through advocacy, workshops, seminars, training, and apprenticeship development. We then called for the involvement of all stakeholders, the scientific community, and information professionals to encourage them to continue working together in building a good data management ecosystem through innovative and collaborative programs. The results of this study could be a policy recommendation for the development of the status of library functions by the supervisory authority, the National Library of the Republic of Indonesia. The scientific community could use them to raise awareness and capacity for research data management from all institutions as data owners (scientific community) and data managers (data librarians).